Social attention in ASD: A review and meta-analysis of eye-tracking studies - Chita-Tegmark, Meia (Research in developmental disabilities, 2016)
•Data from 38 articles using eye-tracking has been used in a meta-analysis to investigate social attention in ASD compared to TD controls.•Individuals with ASD spend less time attending to social stimuli than TD controls (d=0.55).•Social attention in ASD was most impacted when stimuli had a high social content (showed more than one person). Determining whether social attention is reduced in Autism Spectrum Disorder (ASD) and what factors influence social attention is important to our theoretical understanding of developmental trajectories of ASD and to designing targeted interventions for ASD. This meta-analysis examines data from 38 articles that used eye-tracking methods to compare individuals with ASD and TD controls. In this paper, the impact of eight factors on the size of the effect for the difference in social attention between these two groups are evaluated: age, non-verbal IQ matching, verbal IQ matching, motion, social content, ecological validity, audio input and attention bids. Results show that individuals with ASD spend less time attending to social stimuli than typically developing (TD) controls, with a mean effect size of 0.55. Social attention in ASD was most impacted when stimuli had a high social content (showed more than one person). This meta-analysis provides an opportunity to survey the eye-tracking research on social attention in ASD and to outline potential future research directions, more specifically research of social attention in the context of stimuli with high social content.